Mencegah Investasi Bodong Dengan Literasi Pasar Modal Dikalangan Siswa SMA St. Josef Pangkal Pinang - Gulo, Yupiter (UKInstitute, 2023)
The domination of the millennial and Z generations in increasing the number of investors on the Indonesia Stock Exchange, IDX, since the past year is truly encouraging as a strong indicator of confidence in Indonesia's economic progress, but it must be followed by a continuous and effective capital market literacy program to avoid and prevent fraudulent investment practices. Center for Research and Community Service Trisakti School of Management provided training to around 250 students of SMA St. Josef Pangkal Pinang as an effort to increase investment and capital market literacy, as well as to prevent the effects of fraudulent investments that are increasingly prevalent. The results of this training were very good, because students gave positive responses and significantly increased awareness of the importance of investment knowledge before becoming actors and investing in the capital market. Abstrak: Dominasi generasi milenial dan Z dalam peningkatan jumlah investor di Bursa Efek Indonesia sejak satu tahun terakhir sungguh menggembirakan sebagai indikator kuat kepercayaan pada kemajuan ekonomi Indonesia, namun harus diikuti dengan program literasi pasar modal yang terus menerus dan efektif untuk menghindari dan mencegah praktek investasi bodong. Pusat Penelitian dan Pengabdian Kepada Masyarakat Trisakti School of Management memberikan pelatihan kepada sekitar 250 siswa SMA St. Josef Pangkal Pinang sebagai upaya meningkatkan literasi investasi dan pasar modal, serta untuk mencegah pengaruh investasi bodong yang semakin marak terjadi. Hasil pelatihan ini sangat baik, karena siswa memberikan respon positif dan signifikan peningkatan kesadaran pentingnya pengetahuan investasi sebelum menjadi pelaku dan berinvestasi di pasar modal.